Inhibition of Zinc Dendrite Growth in Zinc‐Based Batteries - Lu, Wenjing; Xie, Congxin; Zhang, Huamin; Li, Xianfeng (ChemSusChem, 2018)
Zinc deposition and dissolution is a significant process in zinc‐based batteries. During this process, the formation of zinc dendrites is pervasive, which leads to the loss of efficiency and capacity of batteries. The continually growing dendrites will finally pierce the separator and cause the batteries to short circuit. Thus, employing effective methods to inhibit the formation and growth of zinc dendrites is vital for the practical application of zinc‐based batteries. This Minireview first clarifies the formation and growth principles of zinc dendrites. Then, the research and development of methods to solve the problem of zinc dendrites are reviewed, including ways to suppress the further formation and growth of dendrites as far as possible, to minimize the adverse effects of dendrites, along with ways to produce dendrite‐free deposition processes. The mechanisms, advantages, drawbacks, and perspectives of these methods are illustrated. Thus, this overview of these methods will aid understanding of the formation process of zinc dendrites and provide an extensive, comprehensive, and professional reference to resolve the problem of zinc dendrites completely. Growth misconduct: Zinc deposition and dissolution is a significant process in zinc‐based batteries, whereby the formation of zinc dendrites can lead to the loss of efficiency and capacity of the batteries. This Minireview concerns the formation and growth principles of zinc dendrites, along with the effective methods to solve the zinc dendrite problem in zinc‐based batteries.